Adaptation of SBToolPT to office buildings - Barbosa, José Amarilio (2013)
The few available sustainability assessment tools applicable in Portugal are oriented for residential buildings. Nevertheless, the impacts of office buildings have been rising mainly due to an increase in the energy consumption for cooling and heating. This way, due to the growing environmental impact of office buildings, the development of Building Sustainability Assessment (BSA) tools to assess the sustainability of this type of buildings is necessary and important to guide and to boost the construction sector towards sustainable development. The main objective of this work was to develop a sustainability assessment tool aimed at office buildings based in SBToolPT-H. The work includes the definition of the tool’s framework and assessment method, as well as the Portuguese benchmarks and weighting system used in the aggregation. In order to promote the practical use of this tool, an evaluation guide was also developed in which there is detailed information about calculation methods and aggregation models. The methodology presented in this paper is based on a list of indicators that are assessed by comparison with Portuguese reference practices (benchmarks).